2015
DOI: 10.1039/c5ra12218j
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell differentiation on conducting polyaniline

Abstract: Polyaniline is a promising conducting polymer with broad application potential in biomedicine. Its medical use, however, requires both biocompatibility and suitable physico-chemical and surface properties. The microstructure, electrical properties, and surface characteristics of polyaniline salt, polyaniline base, and polyaniline deposited with biologically active poly(2-acrylamido-2-methyl-1-propanesulfonic acid) were revealed using atomic force microscopy, contact angle measurements, and Raman spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 37 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…Consequently, it can be concluded that introducing PAMPSA into the polymer bulk during synthesis notably affected NIH/3T3 cell proliferation in comparison with reference and pristine polyaniline. These results correspond to observing the preferable behavior of mouse embryonic stem cells on pristine PANI forms, in comparison with PANI deposited with PAMPSA [ 14 ].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Consequently, it can be concluded that introducing PAMPSA into the polymer bulk during synthesis notably affected NIH/3T3 cell proliferation in comparison with reference and pristine polyaniline. These results correspond to observing the preferable behavior of mouse embryonic stem cells on pristine PANI forms, in comparison with PANI deposited with PAMPSA [ 14 ].…”
Section: Resultssupporting
confidence: 83%
“…An interesting phenomena was observed for polyaniline samples that contained PAMPSA in the reaction mixture. As previously published, a significant decrease in γ tot occurred when pristine polyaniline substrate was doped with PAMPSA [ 14 ]. In the present study, in the case of PANI-PAMPSA-1:1, the values obtained for the surface energy corresponded to PANI doped with PAMPSA.…”
Section: Resultsmentioning
confidence: 53%
“…Preparation of ESc R1 line-derived cardiomyocytes from the HG8 clone were described previously 19 , 20 . Purified cardiomyocytes were seeded onto reference tissue culture dishes and onto all tested polyaniline surfaces.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…Neural progenitors were isolated from ganglionic eminences of embryonic brain (13.5 dpc) 19 , 21 and expanding in neurobasal media DMEM:F12 with B27 and N2 supplements, 100 U mL −1 penicillin, 0.1 mg mL −1 streptomycin (Gibco-Invitrogen; USA), 5 ng mL −1 of FGF-2 and 20 ng mL −1 of EGF (PeproTech; USA). Only cells up to passage 3 were used.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…10 Thanks to their easy handling, also using their self-assembling properties, the memristive polymers are the best candidates to obtain memory switching devices able to interface with biological materials. 11 Implementation of the functional properties of living systems into electronic memristive devices has recently obtained with the use of the slime mold PhysarumPolycephalum, a multinuclear unicellular mass of protoplasm. 12,13 To optimize the use of memristive devices as bio-electronic interfaces, it is necessary to asses their biocompatibility measuring the functional viability of the cells adhering to them and moreover assuring their ability to collect the signal directly from the cells.…”
Section: Introductionmentioning
confidence: 99%